Public assistance - Collins, John (Statistical and Social Inquiry Society of Ireland, 1943)
The Public Assistance Act, 1939, which came into operation last August, is now the legal basis of public assistance. It replaced the Poor Relief Acts so far as they related to the administration of relief and combines central control, exercised by the Minister for Local Government and Public Health, with local administration. The County Management Act, 1940, was put into operation on the same date as the Public Assistance Act and, accordingly, public assistance is now administered on the plan which places responsibility for the exercise of the executive functions of the local authority on a manager, reserving to the elected body ultimate financial control.
Irish Social Services: a Symposium
Read March 5th 1943
Keywords: Public Assistance Act 1939; Poor relief; 314.15